2014
DOI: 10.1091/mbc.e13-10-0618
|View full text |Cite
|
Sign up to set email alerts
|

Role of turgor pressure in endocytosis in fission yeast

Abstract: During endocytosis, actin-dependent forces are needed to oppose internal turgor pressure for invagination of the plasma membrane. Live-cell imaging shows that addition of sorbitol to the medium significantly accelerates early steps in the endocytic process and rescues defects of endocytic mutants in fission yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
143
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(148 citation statements)
references
References 57 publications
5
143
0
Order By: Relevance
“…In yeast, actin polymerization is required for endocytosis under normal conditions [4, 5]. This requirement is lessened under conditions of reduced turgor pressure [6, 7] and conversely becomes more stringent when turgor pressure is increased [7]. Finally, correlative light- and electron-microscopy measurements indicate that membrane bending is always preceded by actin polymerization [8], although this finding has been disputed by electron-microscopy studies using other methods [9].…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, actin polymerization is required for endocytosis under normal conditions [4, 5]. This requirement is lessened under conditions of reduced turgor pressure [6, 7] and conversely becomes more stringent when turgor pressure is increased [7]. Finally, correlative light- and electron-microscopy measurements indicate that membrane bending is always preceded by actin polymerization [8], although this finding has been disputed by electron-microscopy studies using other methods [9].…”
Section: Introductionmentioning
confidence: 99%
“…A calculation based on the total number of type-I myosins in fission yeast (10), assuming that each one can generate 2 pN of force, suggested that they could overcome the turgor pressure, but only over a smaller region of radius 10 nm. The geometric arrangement of myosins that would supply forces with the correct orientation and distribution is also not known.…”
Section: Alternative Mechanismsmentioning
confidence: 99%
“…Recent theoretical work on CME in yeast has treated the mechanics of forces generated by actin polymerization, as well as the intrinsic curvature of the clathrin coat that accumulates on the cell membrane (5)(6)(7)(8). To date, however, it is not known how actin and other curvature-generating proteins can produce enough force to overcome the large turgor pressure in yeast (9,10). Here we explore the hypothesis that increasing the membrane permeability at the endocytic site can locally reduce the turgor pressure and thus facilitate endocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Pa [32,33]) inside yeast cells [34]. Under such high pressure, theoretical studies suggest that the force needed to initiate membrane invagination is on the order of 3000pN [35,36] and actin polymerization is thought to provide the driving force.…”
Section: Introductionmentioning
confidence: 99%